Cross-sibling effects on divorce in the Netherlands. (December 2017) - de Vuijst, Elise; Poortman, Anne-Rigt; Das, Marjolijn; van Gaalen, Ruben
Abstract: Parental divorce has repeatedly been shown to increase the risk of divorce for offspring, but research on the influence of other social ties is scarce. This study examines the association of divorce between siblings and whether such an association varies under specific sibship characteristics. Hypotheses were tested using event history models on five complete Dutch birth cohorts (1970–1974), derived from register data. Married individuals (N = 64677) and their sibling were followed from 2000 up to 2012. Results show that individuals with a divorced sibling had a higher risk of divorce even after correcting for a number of shared background factors, including parental divorce. The divorce of a younger sibling had a weaker association with an individual's divorce risk than the divorce of an older sibling, and the effect of sibling divorce weakened over time.